2007
DOI: 10.1111/j.1601-0825.2006.01267.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal and oral microbiological status of an adult population undergoing haemodialysis: a cross‐sectional study

Abstract: On the basis of the findings presented here, we cannot associate ESRD with more severe periodontal destruction. Although HD patients presented a higher number of periodontopathic microorganisms than the matched controls, a prolonged duration of HD did not bear a statistically significant relationship with the percentage of sites with LPA > or =3 mm, specific microbiota or composition of biofilm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
56
2
14

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 33 publications
7
56
2
14
Order By: Relevance
“…9 Castillo et al reported that the mean number of teeth in dialyzed patients with the mean age of 61.5 ± 18.04 was 19.8 ± 8.5. 10 However, Kanjanabuch et al indicated that patients undergoing peritoneal dialysis had significantly less teeth than those in the control group. According to those authors, the difference in the number of teeth between the two groups is not caused by the changes in the structure of alveolar bone, as in both groups the bone density was comparable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Castillo et al reported that the mean number of teeth in dialyzed patients with the mean age of 61.5 ± 18.04 was 19.8 ± 8.5. 10 However, Kanjanabuch et al indicated that patients undergoing peritoneal dialysis had significantly less teeth than those in the control group. According to those authors, the difference in the number of teeth between the two groups is not caused by the changes in the structure of alveolar bone, as in both groups the bone density was comparable.…”
Section: Discussionmentioning
confidence: 99%
“…Cengiz et al, Brito et al, Castillo et al, Bots et al and Bayraktar et al also did not find any statistically important difference in the number of teeth between dialyzed patients and control groups. [8][9][10][11][12] According to Brito et al, the average number of teeth in hemodialyzed patients with the mean age of 50 ± 10 was 17.7 ± 6.4, and in patients undergoing peritoneal dialysis with the mean age of 52 ± 12 was 17.3 ± 6.5. 9 Castillo et al reported that the mean number of teeth in dialyzed patients with the mean age of 61.5 ± 18.04 was 19.8 ± 8.5.…”
Section: Discussionmentioning
confidence: 99%
“…10 Contrarily, others showed that the periodontal condition was not different among these subjects. 11,12 Because of the heterogeneity in findings of these studies, the link of periodontal disease with CKD are still exploring by researchers. The purposes of this study were to compare the prevalence of periodontitis and periodontal status of chronic kidney disease patients with those in non-chronic kidney disease patients and to explore the relationship between periodontitis and chronic kidney disease in a group of Vietnamese patients.…”
Section: Introductionmentioning
confidence: 99%
“…A insuficiência renal crônica (IRC), além de trazer uma série de alterações sistêmicas que interferem diretamente no tratamento odontológico, leva também ao aparecimento de manifestações bucais (CASTILLO et al, 2007).…”
Section: Manifestações Oraisunclassified
“…As alterações da saliva compreendem alterações na sua composição e diminuição do fluxo salivar. A xerostomia poderia também aumentar o risco de cáries cervicais (BOTS et al, 2007;CASTILLO et al, 2007;IMIRZALIOGLU et al, 2007;ROBERTS, 2005;MARTINS et al, 2006;PROCTOR et al, 2005;SHARMA;PRADEEP, 2007 O hiperparatireoidismo secundário também poderia estar relacionado com alterações periodontais ao destruir tecido ósseo produzindo um alargamento do ligamento, muitas vezes com severa destruição periodontal e mobilidade dentária (PROCTOR et al, 2005).…”
Section: Manifestações Oraisunclassified